Impacts of trypanosomosis on land-use and the environment in Africa: State of our knowledge and future directions - Reid, Robin S. (OAU/STRC, 1999)
To understand the environmental impacts of controlling trypanosomosis, there are two principle questions to answer: 1) How does controlling trypanosomosis affect the pattern and rate of land-use/land cover change? 2) If these changes occur, how do they affect ecosystem structure and function? For more than half a century, natural history observations have led scientists and resource managers to speculate about the answers to these questions, but only recently have quantitative studies been conducted that rigorously assess impacts. Most of the impact studies have focused on the first rather than the second question because of its immediate nature. Even concerning land-use/land cover impacts, very few of these quantitative studies have been designed so that the impacts of trypanosomosis control can be distinguished from other factors that cause land-use/land cover change. Even when good comparative sites are available for study, establishing cause and effect is difficult. However, accumulating evidence shows that tsetse/trypanosomosis and land-use/land cover change are strongly linked in some locations in Africa and weakly linked in others. These changes in land-use/land cover can have unanticipated impacts on biological diversity and vegetative structure. These and other results are synthesized into a picture of our current knowledge and future directions about tsetse/trypanosomosis control, land-use and the environment.